Positive effect of Balint group on burnout and self-efficacy of head nurses in China: a randomized controlled trial - Shan, Qu; Leonhart, Rainer; Zhijuan, Xie; Minjie, Zheng; Xinxin, Shi; Xinzhu, Bai; Xiangyan, Kong; Fritzsche, Kurt (Frontiers in Psychiatry, 2024)
Background Burnout is common among nurses and can lead to negative outcomes of medical care. This study aimed to explore the effectiveness of Balint groups to reduce burnout in head nurses in a Chinese hospital. Methods This was a randomized controlled trial with a pre- and post-test. A total of 80 head nurses were randomly assigned to either a Balint group (n = 40) or a control group (n = 40). Participants participated in Balint group for a period of 3 months. Participants in both groups completed the Maslach Burnout Inventory-Human Services Survey and the General Self-Efficacy Scale at the beginning and end of the study. Balint group members also completed the Group Climate Questionnaire-Short Form. Results In the Balint group, 33 participants attended all Balint groups, while the 40 participants in the control group had no intervention. Analysis of variance with repeated measures demonstrated a statistically significant difference on the Maslach Burnout Inventory subscale of sense of personal achievement (F = 9.598, p = 0.003) between the Balint and control groups. However, there were no significant differences between the groups on the subscales of emotional exhaustion (F = 0.110, p = 0.740) and depersonalization (F = 0.75, p = 0.387), and the General Self-Efficacy Scale (F = 0.709, p = 0.403). Conclusions Balint groups helped reduce burnout among head nurses in terms of personal achievement.